An Ecological Approach Towards Classification of Coastal Vegetation of India II. Estuarine Border Vegetation - Ananda Rao, T.; Sastry, A. R. K. (Indian Forester, 1974)
Studies on the Indian estuarine border vegetation have gained a steady importance in the recent years and considerable valuable data have been gathered especially with regard to floristic, edaphic and ecological aspects by various worhers and in particular by the Ecoloay Unit in the Botanical Survey of India, which is engaged in ecological studies on Indian coastal vegetation for the last 13 years. Based on this knowledge, an attempt is now made to analyse and reclassify the Tidal swamp forests is greater detail but adhering to the original framework of Champion and Seth (1968). In the present paper, this vegetational type has been sub-divided into two types: Euestuarine and Prostuarine; and the Prostuarine complex type has been further sub-divided into three sub-types: Tidal Mangrove, Euhyaline and Probyline Under each type and their sub-types the salient fetures such as plant groupings, topography, indicator plants and edaphic characteristics have been discussed.